Sojourner Students' Adjustment: Do They Need to Lower Their Normative Achievement Goal Orientation to Remain Confident and Survive - Faizah, Lailatul; Rifameutia, Tjut (Makara Human Behavior Studies in Asia, 2019)
Adjustment is very important for college students, especially for sojourner students. Even though sojourner students initially had high academic self-efficacy, it does not necessarily help them to survive their new academic learning environment. This study argues that normative achievement goal orientation moderates the relationship between academic self-efficacy and academic adjustment among sojourner students. To test the hypothesis, data was collected from 296 first-year sojourner students from 16 public universities in Indonesia and analyzed using Hayes moderator analysis. The results showed that normative achievement goal orientation negatively moderated the relationship between academic self-efficacy and academic adjustment (β = −0.09, SE = 0.04, p = 0.02). The results of the present study indicate that the role of normative achievement goal orientation is maladaptive. By using the big fish—little pond phenomena at the discussion, we make sense of the results with the aim of advancing current knowledge. We proposed collaborative learning as a method to lower first-year sojourner students’ normative achievement goal orientation, thus helping them to increase academic adjustment.